Modification and patterning of thiolate-anchored self-assembled monolayers with UV light - Zharnikov, Michael; Terfort, Andreas (Advanced materials interfaces, 2025)
Along with their ability to redefine the chemical and physical properties of surfaces and interfaces, self-assembled monolayers (SAMs) may serve as versatile resists and templates for lithography, providing chemical, morphological, and biological patterns. A particularly useful approach in this context is photolithography with UV light. Applied to thiolate-anchored SAMs on coinage metal substrates, UV light induces the oxidation of the anchoring groups and damage to the SAM matrix, with the rates and extent depending strongly on the wavelength. Here, these processes for different types of thiolate SAMs are discussed, and it is shown that the potential of UV lithography with SAM templates can be noticeably extended if it is combined with the subsequent exchange reaction with a molecular substituent capable of assembling on the given substrate. Since the extent of the substitution can be controlled by the irradiation dose, the final chemical composition can be flexibly tuned, allowing the preparation of functional binary SAMs and the creation of complex gradient-like patterns. Using primary bioinert monolayers, templates for nonspecific and specific adsorption of biomolecules and biopolymer brushes are fabricated. The combination of electrostatic engineering of interfaces and promoted exchange reaction allows location-selective work function modification for organic electronics devices in a circuit.
Zuerst veröffentlicht: 8. Juni 2025
Gesehen am 17.10.2025